Cost-effective and strongly integrated fabric-based wearable piezoelectric energy harvester. (September 2020) - Kim, Jaegyu; Byun, Seoungwoo; Lee, Sangryun; Ryu, Jeongjae; Cho, Seongwoo; Oh, Chungik; Kim, Hongjun; No, Kwangsoo; Ryu, Seunghwa; Lee, Yong Min; Hong, Seungbum
Abstract: Fabric-based wearable electronics are becoming more important in the fourth industrial revolution (4IR) era due to their connectivity, wearability, comfort, and durability. Conventional fabric-based wearable electronics have been demonstrated by several researchers, but still need complex methods or additional supports to be fabricated and sewed in clothing. Herein, a cost-effective, high throughput, and strongly integrated fabric-based wearable piezoelectric energy harvester (fabric-WPEH) is demonstrated. The fabric-WPEH has a heterostructure of a ferroelectric polymer, poly(vinylidene fluoride-co-trifluoroethylene) [P(VDF-TrFE)] and two conductive fabrics via simple fabrication of tape casting and hot pressing. Our fabrication process would enable the direct application of the unit device to general garments using hot pressing as graphic patches can be attached to the garments by heat press. Simulation and experimental analysis demonstrate fully bendable, compact and concave interfaces and a high piezoelectric d 33 coefficient (−32.0 pC N −1 ) of the P(VDF-TrFE) layer. The fabric-WPEH generates piezoelectric output signals from human motions (pressing, bending) and from quantitative force test machine pressing. Furthermore, a record high interfacial adhesion strength (22 N cm −1 ) between the P(VDF-TrFE) layer and fabric layers has been measured by surface and interfacial cutting analysis system (SAICAS) for the first time in the field of fabric-based wearable piezoelectric electronics. Graphical abstract: Image 1 Highlights: We developed a highly flexible fabric-based wearable piezoelectric energy harvester. Our fabrication process using hot pressing and tape casting is very simple and easy to control. The energy harvester has a record high interfacial adhesion strength between the piezoelectric layer and the fabrics layers. Our energy harvester has potential in the fields of embedded wearable applications.